Differences in bacterial composition between vascular epiphyte and parasitic plants living on the same host plants - HOANG DANG KHOA DO; ARIF LUQMAN; MINH THIET VU; HOANG DANH NGUYEN; YOHANES KARTJITO PUTRO; ELSALISA AINUR ROFIQA; HERI SANTOSO; ALFINDA NOVI KRISTANTI; SUCIPTO HARIYANTO; LE MINH BUI; YOSEPHINE SRI WULAN MANUHARA; ANJAR TRI WIBOWO (Society for Indonesian Biodiversity, 2022)
Abstract. Do HDK, Luqman A, Vu MT, Nguyen HD, Putro YK, Rofiqa EA, Santoso H, Kristanti AN, Hariyanto S, Bui LM, Manuhara YSW, Wibowo AT. 2022. Differences in bacterial composition between vascular epiphyte and parasitic plants living on the same host plants. Biodiversitas 23: 5798-5805. Epiphytic and parasitic plants can grow and complete their life cycle while attached to the host. Therefore, the interactions between these plants and their host provide profound evidence for co-evolution. During these symbiotic interactions, bacteria are actively exchanged between parasitic and epiphytic plants with their hosts. Since epiphytes and parasitic plants have different ways of life, they might assemble their bacterial community differently despite living in the same host. However, direct microbiome comparisons between epiphytic and parasitic plants colonizing the same host have never been evaluated. In this study, we examined the bacterial compositions of the epiphytic Hoya sp. and parasitic Dendrophthoe sp. that grow in two host species, frangipani (Plumeria sp.) and teak (Tectona grandis). The results revealed that bacterial compositions in the root of Hoya sp. are highly similar to the peripheral tissue of the host stem. In contrast, bacterial composition in the haustoria of Dendrophthoe sp. is quite distinct from the host. These results revealed that epiphytes and parasitic plants acquire and assemble their microbiome differently, despite living in the same host species. These differences might originate from different nutrient acquisition strategies between the two plants.